Pakistan-Russia Relations within the Framework of the SCO: A Regional Analysis - Hira Yaqoob; Abeeda Qureshi (NUST Journal of International Peace and Stability)
Pakistan and Russia have shared geographical proximity, but historically, this proximity did not translate into extensive cooperation due to Pakistan's alignment with the Western bloc during the Cold War and India’s strong relations with Russia. Pakistan's official membership in the Russian-cofounded Shanghai Cooperation Organization (SCO) in 2017 marked a significant development in bilateral relations. While considerable research exists on the SCO and its progress, studies focusing specifically on Pakistan-Russia relations through the SCO framework remain limited. Pakistan’s membership in the SCO coincided with important regional developments, including the Taliban’s takeover of Afghanistan, the resurgence of regional terrorism, increased US-China competition, India’s strengthening ties with the U.S., the Russia-Ukraine conflict, and the hesitancy of Western countries to engage with Russia. An analysis of Pakistan-Russia relations from 2015 to 2024, grounded in the theory of complex interdependence, indicates progress in cooperation and potential for enhanced collaboration in areas such as security, energy, and cultural exchange. Shared interests in China and the Central Asian region also highlight the possibility of increased regional cooperation through the SCO platform. However, several factors have posed challenges to furthering these relations, including tense Indo-Pak relations, India’s membership in the SCO and historical ties with Russia, perceptions of Pakistan's susceptibility to external pressures, and regional instability linked to terrorism. Addressing these challenges requires proactive engagement to fully leverage the opportunities presented by the SCO to encourage Pakistan-Russia relations and collaboration.